Putting the Brakes on the Preventive State: Challenging Residency Restrictions on Child Sex Offenders in Illinois under the Ex Post Facto Clause - Olson, Michelle (2010)
This Comment explores whether a viable challenge to residency restrictions on child sex offenders in Illinois exists under the Ex Post Facto Clauses of the federal and state constitutions. It also recounts the history of sex offender regulation in Illinois and explores the social and political environment that fostered the emergence of residency restrictions in the state. Part I provides a brief overview of the history and purpose of the Ex Post Facto Clause. It also highlights the recent resurgence of preventive lawmaking; that is, laws that work to prevent crime rather than detect and investigate it, and laws that impose direct restraints on the liberty of those considered particularly dangerous by the state. Part II briefly recounts the legislative history of sex offender regulation in Illinois, and provides an overview of the political and social realities that shaped the legislative debate. Part III uses recent state court decisions in Illinois, Indiana, and Kentucky to evaluate the constitutionality of residency restrictions on child sex offenders in Illinois, ultimately arguing that such restrictions violate the ex post facto clauses of the federal and state constitutions. Finally, this Comment concludes by considering the need for judicial intervention given the resurgence of the preventive state